The Effects of Repetitive Use and Pathological Remodeling on Channelrhodopsin Function in Cardiomyocytes - Ördög, Balázs; Teplenin, Alexander; De Coster, Tim; Bart, Cindy I.; Dekker, Sven O.; Zhang, Juan; Ypey, Dirk L.; de Vries, Antoine A. F.; Pijnappels, Daniël A. (Frontiers in Physiology, 2021)
Aims: Channelrhodopsins (ChRs) are a large family of light-gated ion channels with distinct properties, which makes the selection of a ChR variant for a given application of great importance. However, data to guide such selection for cardiac optogenetic applications are lacking. Therefore, we investigated the functioning of different ChR variants in normal and pathological hypertrophic cardiomyocytes subjected to various illumination protocols. Methods and Results: Isolated neonatal rat ventricular cardiomyocytes (NRVMs) were transduced with lentiviral vectors to express one of the following ChR variants: H134R, CatCh, ReaChR or GtACR1. NRVMs were treated with phenylephrine (PE) to induce pathological hypertrophy (PE group) or left untreated (CTL group). In these groups, ChR currents displayed unique and significantly different properties for each ChR variant upon activation by a single 1-s light pulse (1 mW/mm2: 470, 565 or 617 nm). The concomitant membrane potential (Vm) responses also showed a ChR variant-specific profile, with GtACR1 causing the smallest increase in average Vm during illumination (Vplateau: -38 mV) as compared to a Vplateau >-20 mV for the other ChR variants. Upon repetitive activation at increasing frequencies (10-ms pulses at 1-10 Hz for 30 s), peak currents, important for cardiac pacing, decreased with increasing activation frequencies by 17-78% (p<0.05), while plateau currents, critical for arrhythmia termination, decreased by 10-75% (p<0.05), both in a variant-specific manner. In contrast, the corresponding Vplateau remained largely stable. Importantly, current properties and Vm responses were not statistically different between the PE and CTL groups, irrespectively of the variant used (p>0.05). Conclusions: Our data show that ChR variants function equally well in cell culture models of healthy and pathologically hypertrophic myocardium, but show strong, variant-specific use-dependence. This use-dependent nature of ChR function should be taken into account during the design of cardiac optogenetic studies and the interpretation of the experimental findings thereof.